A STUDY OF URBAN PLACEMAKING EVOLUTION CHANGES AT PASAR SANTA JAKARTA - Ruth E. Oppusunggu; Melissa Tjoeputri; Martin L. Katoppo (International Journal on Livable Space, 2018)
AbstractTraditional markets -where bargaining is method of trading- are still one of urban fabrics that offer sense of places, and Jakarta has 153 traditional markets managed by Jakarta regional owned enterprise. Numerous of these traditional markets had been renovated into layers of concrete buildings, but many are almost paralyzed in competing with shopping malls and the new way of trading, online shopping. Pasar Santa is still one of a kind. In 2014, Santa became the hippest gathering place and prestige marketplace for the emerging creative communities and young people -a new generation of vendors and buyers- while it still maintained its everyday needs such as fresh food, groceries and housewares. Santa -with its 1151 kiosks – succeeded to compete shopping malls and became one of the must-seen place in Jakarta. But in 2015, it died down causing farther businesses left. This paper captures the placemaking research of Santa's evolution stages -especially in the end of 2016 to the end of 2017 when DAG conducted participatory action research- and analyzes the reasons behind the changing characteristics and public perception. The study shows that community's collaboration and design can fabricate Santa into vibrant urban destination again. Key words: traditional market, placemaking, creative community, design as generator, community participation/ collaboration